The Role of the Posterior Temporal and Medial Prefrontal Cortices in Mediating Learning from Romantic Interest and Rejection. (18th April 2013) - Cooper, Jeffrey C.; Dunne, Simon; Furey, Teresa; O'Doherty, John P.
Abstract : Romantic interest or rejection can be powerful incentives not merely for their emotional impact, but for their potential to transform, in a single interaction, what we think we know about another person—or ourselves. Little is known, though, about how the brain computes expectations for, and learns from, real-world romantic signals. In a novel "speed-dating" paradigm, we had participants meet potential romantic partners in a series of 5-min "dates, " and decide whether they would be interested in seeing each partner again. Afterward, participants were scanned with functional magnetic resonance imaging while they were told, for the first time, whether that partner was interested in them or rejected them. Expressions of interest and rejection activated regions previously associated with "mentalizing, " including the posterior superior temporal sulcus (pSTS) and rostromedial prefrontal cortex (RMPFC); while pSTS responded to differences from the participant's own decision, RMPFC responded to prediction errors from a reinforcement-learning model of personal desirability. Responses in affective regions were also highly sensitive to participants' expectations. Far from being inscrutable, then, responses to romantic expressions seem to involve a quantitative learning process, rooted in distinct sources of expectations, and encoded in neural networks that process both affective value and social beliefs.